AKTIVITAS ANTIBAKTERI EKSTRAK DAUN JAMBU BIJI (Psidium guajava,L.,) DENGAN PENYARI ETANOL DAN KLOROFORM TERHADAP PERTUMBUHAN Staphylococcus aureus - Liana Fijriati; Luthfi Hidayat Maulana; Pudjono Pudjono (Prodi Farmasi Fakultas Sains dan Teknologi Universitas Peradaban, 2022)
The high mortality rate in the world, especially in tropical areas such as Indonesia, is one of the causes of infectious diseases. Infectious disease is one of the problems in the health sector that many Indonesian people suffer from which from time to time continues to grow. This study aims to determine the antibacterial activity of guava leaf extract with 70% ethanol and chloroform extract against Staphylococcus aureus based on the diameter of the inhibition zone. The concentrations of the extracts used were 5%, 10%, and 15%. For the positive control, amoxicillin was used, and the negative control was 10% DMSO. Extraction was carried out by maceration by soaking 250 grams of guava leaf powder in 500 ml of 70% ethanol. The filtrate from the maceration was filtered, then the residue was macerated again with 500 ml of chloroform filter, then evaporated in a rotary evaporator. Produces a thick extract in ethanol as much as 10 grams, and in chloroform as much as 6 grams. The extract obtained was then tested for its antibacterial activity using Nutrient agar media by well diffusion. The results obtained showed the presence of antibacterial activity in each filter, namely 5%, 10% and 15% ethanol extract, respectively, of 4.6 mm; 8mm and 10 mm. Meanwhile, in 5% , 10% and 15% chloroform, respectively, they were 4.3 mm; 7.6 mm and 10.3 mm. Positive control of 20 mm amoxicillin and negative control with 10% DMSO solvent did not show any antibacterial activity. From the results of the study, it was also found that the concentration of 15% in both extracts had the highest antibacterial activity in inhibiting the growth of Staphylococcus aureus. Keywords: Guava leaves, Staphylococcus aureus, antibacterial, inhibition, well diffusion.